EVALUATION OF TAXATION PROVISIONS ON TRANSACTIONS E-COMMERCE ON THE MARKETPLACE PLATFORM - Posma Leonardo; Christine Tjen (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This research is based on the problem of the development of transactions e-commerce that do not necessarily boost state revenues from the taxation sector. The Directorate General of Taxation has made an affirmation regarding e-commerce by issuing SE-62 / PJ / 2013 dated December 27, 2013 concerning Affirmation of Provisions on Taxation of Transactions E-commerce, where transactions e-commerce are subject to the same tax as conventional business actors. This study aims to analyze the application of SE-62 / PJ / 2013 at PT Bukalapak.com and provide recommendations to PT Bukalapak.com related to the taxation aspect of transactions e-commerce. The object of the research is PT Bukalapak.com with the Tax Division as a unit of analysis. The research instrument uses interviews with PT Bukalapak.com and questionnaires to sellers who transact using the marketplace platform. The conclusion of the study is that PT Bukalapak.com does not implement or apply specific provisions for users of the Bukalapak application, this refers to the taxation system carried out in Indonesia, namely self assessment. Lack of tax knowledge on taxation obligations causes less success in maximizing tax payments on transactions e-commerce. PT Bukalapak.com has the initiative to become a partner of the taxation authority.